Seawater carbonate chemistry and trophic structure of Arctic plankton assemblages - Koji Sugie; Bingzhang Chen; Shigeto Nishino; Toru Hirawake (PANGAEA, 2025)
Here we conducted incubation experiments to determine the temperature and CO2 sensitivities of marine phytoplankton growth and microzooplankton grazing in the western Arctic Ocean, where rapid climate change is taking place. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-11-26.